Characterization and Dynamics of Sheep Farming Systems in the Arid Steppe of Eastern Algeria: RESEARCH PAPER - M. Douh; L. Karkour; S. Chekchaki; O. Rahal; I. Cherif (Annals of Arid Zone, 2025)
Sheep farming is a vital component of rural livelihoods in Algeria’s arid regions, especially in the Tebessa area. This study examines the spatial distribution and economic characteristics of sheep production farms in these dry lands, with a focus on management strategies, resource utilization, and socio-economic and environmental challenges. A survey of 161 agro-pastoralists revealed diverse farming systems as influenced by traditional practices and harsh climatic conditions. Two primary flock management models and varied feeding strategies, integrating pasture and crop residues, were identified. While direct grazing supports satisfactory economic performance, larger farms face constraints related to feed supply and input costs. About 70% of farms follow traditional practices, while 30% are transitioning toward semi-intensive systems, encompassing both changes in genetic selection and feed management. The results underscore both the resilience and vulnerability of sheep farming in arid zones, emphasizing the need for improved feed resources, support for semi-intensive transitions, and policies that address socio-economic and climate-related challenges to ensure sustainable development.